Mental Fatigue From Smartphone Use Reduces Volume-Load in Resistance Training: A Randomized, Single-Blinded Cross-Over Study. Issue 4 (August 2021) - Gantois, Petrus; Lima-Júnior, Dalton de; Fortes, Leonardo de Sousa; Batista, Gilmário Ricarte; Nakamura, Fábio Yuzo; Fonseca, Fabiano de Souza
We investigated the acute effects of mental fatigue induced by 30-minute use of smartphone social network apps on volume load in resistance training among recreationally trained adults. Sixteen (n = 16) adults of both sexes performed three sets of a half back-squat exercise to failure with 80% of 15RM, interspersed with 3-minutes of passive recovery between sets, before and after two different cognitive tasks: (a) use of smartphone social network apps; and (b) watching a documentary. We assessed mechanical variables and ratings of perceived exertion during the strength exercise. Relative to the documentary-viewing control condition, a 30-minute exposure to smartphone social network apps led participants toward increased perception of mental fatigue ( p = 0.004) and lower volume-load during the strength exercise ( p = 0.006). There were no significant differences in perceived exertion between conditions ( p = 0.54), participants' motivation ( p = 0.277), intra-set mechanical variables ( p > 0.05), or blood lactate concentrations ( p = 0.36). Our findings of an isolated possible higher-than normal RPE without changes in physiological variables, accompanying the lower volume-load in the mentally-fatigued participants support psychological, rather than physiological, bases for mental fatigue effects.